ANALISIS PEMANFAATAN DEFINISI KONSEP DALAM UU APARATUR SIPIL NEGARA (TINJAUAN DARI ASPEK PREDIKSI MUNCULNYA PROBLEM IMPLEMENTASI) - Pambudi, Argo (Natapraja, 2015)
Multi-factor interpretation of the concept that is used in every public policy often becomes the cause of problems in implementation. This problem arises when there are different interpretations among those who involve in the implementation phase. Problems will be bigger when the differences in interpretation can not be compromised. Therefore improper definition variable of the concept-to be the root causes of this phenomenon of multiple interpretations.Meanwhile, the different perception variable, different interests, different socio-cultural settings and other differences in society are variables that strengthen the foundation of the emergence of these differences. The logical consequence that must be faced in every public policy is that the use of the definition of the concept of right-of-use is a demand that must be met in order to prevent the emergence of various implementation issues derived from the variables mentioned above. This article was written to gain a deep understanding of the right-to aspects related to the use of the definition of the concept in Law No. 5 of 2014 on the Civil State Apparatus. The goal is that it can assert potental material that raises issues of the implementation of the law and can also be used as an academic paper refinement and consideration for the development of policies and / or regulations to implement the Act. Kata kunci: public policy, civilian state apparatus, concept definition